2017
DOI: 10.1016/j.ijmedinf.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Making electronic health records support quality management: A narrative review

Abstract: The findings resonates well with previous reviews, though two factors making EHR support QM seem new, namely: political goals and strategies, and integration of guidelines for clinical conduct. Lacking EHR type specification and diversity in study method imply that there is a strong need for further research on the factors that may make EHR may support QM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Electronic health records are integrated software platforms that are used by health care providers to create, store, update, maintain, and share medical information about patients. Such systems are used in primary, secondary, and tertiary care and seen as essential technologies for modern health care provision (Häyrinen, Saranto, & Nykänen, ; Triantafillou, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic health records are integrated software platforms that are used by health care providers to create, store, update, maintain, and share medical information about patients. Such systems are used in primary, secondary, and tertiary care and seen as essential technologies for modern health care provision (Häyrinen, Saranto, & Nykänen, ; Triantafillou, ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the software selection context of our case is exemplary for many acquisitions of extensive software packages by large public health care providers. A recent review shows how, at least in EHR implementation, all 3 decision‐making rationalities are at play (Triantafillou, ). The lessons learned from this case, in terms of its process and outcome, may thus have value for others sharing the context.…”
Section: Methodsmentioning
confidence: 99%
“…The trend of demand for electronic healthcare was considerable (Ndifon et al, 2016). In another study by Gonzalez (2013), the outstanding merits of national EHR technology are inclusive of -care continuum, reduction in costs, managing medications, long-term strategic point of view and portability, emergency episode management and empowering patients.‖ The inception of proposing implementing EHR in hospitals in Organization for Economic Cooperation and Development (OECD) countries traces back virtually 1990s (Triantafillou, 2017). To highlight implementing EHR and benefits associated with it, Nguyen, Bellucci, and Nguyen (2014) conducted a systematic literature review paper regarding EHR implementation in the hospital around the world.…”
Section: The Emergence Of Ehr and Its Functionalitymentioning
confidence: 99%
“…The research methodology was based on academic literature and searching in various valid databases such as Web of Science, EBSCO, Scopus, and others. As cited by Triantafillou (2017), quality management is a function of three dimensions, which are clinical outcomes, managerial monitoring, and cost-effectiveness. Results of the review of 39 types of research revealed that 29 studies supported the clinical outcomes.…”
Section: Ehr and Quality Managementmentioning
confidence: 99%
See 1 more Smart Citation